2021
DOI: 10.1017/laq.2020.81
|View full text |Cite
|
Sign up to set email alerts
|

An Inka Unku from Caleta Vitor Bay, Northern Chile

Abstract: As insignia of power and prestige, Inka unku (tapestry tunics) communicated the strength and extent of Inka sociopolitical hegemony in the Andes. Of the 36 known full-size examples in museum collections, only one, found in Argentina, comes from outside Peru. This article investigates another recently excavated unku found out of context on Chile's northernmost coast. To confirm its authenticity, we compiled a database showing the technical and stylistic attributes of previous finds for comparison. We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This includes a long rectangular morphology and lack of sleeves. The measurements are within the established averages for width [between 72–79 cm; 6 ] and length [between 79–110 cm; 44 ]; see also Mary Frame [ 12 ]. The unku’s interlocking tapestry technique is certainly of highland origin, as are its checkerboard design and “V”-shaped yoke, which forms a diamond when the piece is laid out fully.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This includes a long rectangular morphology and lack of sleeves. The measurements are within the established averages for width [between 72–79 cm; 6 ] and length [between 79–110 cm; 44 ]; see also Mary Frame [ 12 ]. The unku’s interlocking tapestry technique is certainly of highland origin, as are its checkerboard design and “V”-shaped yoke, which forms a diamond when the piece is laid out fully.…”
Section: Discussionsupporting
confidence: 71%
“…To test the hypothesis that the CV unku was produced by specialized local weavers who incorporated their own symbolic and meaningful elements, our case study focuses on the unku found in Caleta Vitor Bay, northern Chile [ 6 ]. The CV unku is an exceptional example, not only for that area but also for the entire Andean region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation